Laparotomi garis tengah untuk kriptorkismus inguinal unilateral pada kucing Persia campuran - Salsabila , Firda Shafa; Syaputri , Nimas Aldila; Rochma , Oktalavia Dwi Noer; Syafira (ARSHI Veterinary Letters, 2025)
Cryptorchidism is a congenital condition in male cats, characterized by incomplete testicular descent, which increases the risk of neoplasia, torsion, and infertility. A five-year-old intact mixed Persian cat with unilateral cryptorchidism, diagnosed in 2020, presented for elective testicular removal. Despite this, the cat had previously in 2024 sired its offspring. Ultrasonography revealed that the right testis was located in the inguinal region. The procedure included cryptorchidectomy for inguinal testicles and routine castration for external testicles, performed under general anesthesia. An endotracheal tube was placed and intraoperative monitoring ensured patient stability. The postoperative recovery was uneventful, with complete healing within 10–14 days.